Pengungkapan Pertanggungjawaban Sosial Perusahaan (CSRD) dan Pengaruh Sosial terhadap Kinerja Keuangan: Perusahaan Sektor Teknologi di Indonesia - Pujangga Abdillah; Ria Mennita (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The study aims to examine the influence of corporate social responsibility disclosure and social influence on financial performance in Indonesia. Samples were taken using the judgment sampling technique with a total sample of observations. We leverage content analysis, fixed-effects, and random-effects models to examine the effect of engaging in CSRD on financial performance in the technology industry. The empirical study consists of panel data of the top technology companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2021. The results showed that CSRD has an effect on financial performance as measured by Return on Asset (ROA). That is, the higher CSR disclosures made company can improve the company's financial performance. The results of this study also show that social influence has an effect on financial performance. Keywords: Corporate Social Responsibility Disclosure, Social Influence, Financial Performance.